2015
DOI: 10.12681/mms.1375
|View full text |Cite
|
Sign up to set email alerts
|

Meiofaunal Diversityand Nematode Assemblages in Two Submarine Caves of a Mediterranean Marine Protected Area

Abstract: Submarine caves are environments of great ecological interest because of the occurrence of peculiar conditions, such as the attenuation of light and reduced water turnover, which can determine oligotrophic conditions from the entrance to the interior part of the cave. These environmental gradients may influence the distribution of the communities inhabiting submarine caves. In this study we investigated the meiofaunal community and nematode assemblages from the sediments inside and outside two submarine caves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This likely reflected an important role of the immigration of nematode species from adjacent coral reef environments such as Paradesmodora immersa, Pomponema sp., and Zalonema ditlevseni. Other studies in submarine caves have reported different findings with the dominance of either non-selective deposit feeders or omnivores/predators [85,86].…”
Section: Discussionmentioning
confidence: 92%
“…This likely reflected an important role of the immigration of nematode species from adjacent coral reef environments such as Paradesmodora immersa, Pomponema sp., and Zalonema ditlevseni. Other studies in submarine caves have reported different findings with the dominance of either non-selective deposit feeders or omnivores/predators [85,86].…”
Section: Discussionmentioning
confidence: 92%
“…However, some efforts were made in the past (i.e. Wieser 1954;Pesta 1959) and more recently (Palacin and Masalles 1986;Palacín et al 1992;Grimaldi de Zio et al 1982a, b;Villora-Moreno 1996;Sandulli et al 1999;Todaro et al 2006;Ape et al 2015;Janssen et al 2013). Several marine caves in the Mediterranean Sea, Atlantic Ocean and Australia have been investigated for the presence of meiofauna.…”
Section: Meiofauna From Submarine Cavesmentioning
confidence: 99%
“…TRIX index, used to characterizing succinctly the trophic levels of the coastal marine area, shows that Ustica MPA has moderately productive waters with good transparency and average trophic level, highlighting even in autumn, similar characteristics to the open sea. Our research can be considered as a sort of integration of the knowledge of this MPA; in fact, several studies and observation have been conducted on flora, fauna and other topics, principally on the coastal fish and molluscan assemblage (37)(38)(39)(40)(41)(42), but no data have been published on water variables. Water column analyses represent an essential topic in the evaluation of all water environments.…”
Section: Discussionmentioning
confidence: 99%